The effects of clay nanoparticles as reinforcement agent on the properties of starch-protein edible film: article - Azmi, Nurshalina; Hamidon, Fariza (2017)
In order to reduce the environmental damage to the environment, the edible film made from starch-protein was conducted which may replace the non-degradable material which is plastic that commonly used. As to increase the properties of film, the addition of clay to the starch-protein film is made which the objective is to study the mechanical and physical properties of the starch-protein film. The water-vapour permeability (WVP), water solubility and mechanical test (tensile strength and elongation at break was conducted. Montmorillonite (MMT) clay was used in this researched. As the result, in the presence of MMT in the film decreased the value of WVP (3.377×10-9 g/m.s.Pa to 1.0918 ×10-9 g/m.s.Pa) and percentage of water solubility (98.72% to about 50%). The different amount of clay 5%, 10%, 15% and 20% from weight of starch-protein is performed and showed inconsistent result. Result for mechanical properties showed the decreased in tensile strength and elongation at break as the addition of clay to the starch-protein film. At the end of this study, can be conclude that 5% clay film is the most suitable composition for food packaging application. The highest elongation at break for 5% clay film is significantly higher than other.